Production System Design bio-oil of Microalgae with POME as Raw Material For Media Cultivation - Rahmat Wahyudi Nasution; Taufik djatna (Warmadewa University Press, 2018)
Palm Oil Mill Effluent (POME) produced by the Palm Oil Mill as a waste is now being used as a medium for cultivating microalgae for bio-oil raw materials. However, the bio-oil production process from POME raw materials is still limited to lab scale. Therefore, in this project, the analysis of bio-oil production system from microalgae for the development of existing production system. In this paper, the optimization model of bio-oil production from microalgae biomass is simulated into Digital Business Ecosystem (DBE) concept then analyzed to related stakeholders in system and interaction of each process or between fellow stakeholders. And the results are defined in the form of Information Communication and Technology (ICT). The method used for this DBE concept is Unified Modeling Language (UML) which is use case diagram and Business Process Model and Notations (BPMN) diagram. And to predict an increase in yield by using ARM (Association Rule Mining). The results of this study are shown in the use case diagram and BPMN consisting of five communities, namely raw materials community, cultivation community, harvesting community, extraction community and quality control (QC). The process of production and storage of the resulting data is illustrated in the BPMN diagram. In this paper the association rule is used to explore the relationship pattern between Cell Density attributes, Lipid Content and Light Intensity. The integration of association rule with a priori paradigm has succeeded in finding 34 rules with 11 valid rules top rank which have lift > 1 of relation between attributes